Evaluating Sub-Saharan Africa’s COVID-19 Research Contribution: A Preliminary bibliometric Analysis - Asubiaro, Toluwase; Shaik, Hafsah (My University, 2021)
The response to the ongoing COVID-19 pandemic in the science community is unprecedented as indicated by the high number of research publications. Deeper insight into COVID-19 research at regional, and national levels through bibliometric research has revealed different levels of research evolution, depth, contribution, and collaboration patterns. Such reliable and evidence-based information is important for health research planning and policy making. This study aims at providing some evidence-based insight into Sub-Saharan Africa’s preliminary COVID-19 research by evaluating its research contributions, patterns of collaboration, and funding sources. COVID-19 publication data from all the 41 Sub-Saharan African countries was collected from Scopus for analysis. Results show that Sub-Saharan Africa contributed about two percent to global COVID-19 research. South Africa contributed 50.95% of all the COVID-19 publications from Sub-Saharan Africa while USA (28.48%) and the UK (24.47%), the top two external contributors, collaborated with Sub-Saharan African countries three times more than other countries. Collaborative papers between Sub-Saharan African countries - without contributions from outside the region- made up less than five percent of the sample, whereas over 50% of the papers were written in collaboration with researchers from outside the region. Organizations based in USA, UK, and EU funded more than 60% of all the COVID-19 research from Sub-Saharan Africa. More than 60% of all the funding from Sub-Saharan African countries came from South African organizations. This study provides evidence that pan-African COVID-19 research collaboration is low, perhaps due to poor funding and institutional support within Africa. There is a need to forge stronger pan-African research collaboration networks, through funding from Africa’s national and regional government organizations, with the specific objective of meeting COVID-19 healthcare needs of Africans.
Keywords: bibliometric analysis; co-authorship; coronavirus; coronavirus research; COVID-19; international collaboration; research; research collaboration; research funding; Sub-Saharan Africa